Subproductos de cítricos como fuente de fibra dietaria. - Cevallos Jiménez, Janneth del Rocío (2015)
The aim of this research was to know the content of total dietary fiber and its soluble and insoluble fractions in orange byproducts (Citrus sinensis) var. Valencian early (albedo + remains of flavedo, flavedo and exhausted pulp) subjected to a previous process of washing with hot water at 45°C. The total and insoluble dietary fiber were determined by the enzymatic - gravimetric method AOAC 991.43 and AACC 32-07, based on Prosky et. al (1998) and according to the Protocol of Megazime; while the soluble dietary fiber was established by the difference between the values of total dietary fiber and insoluble dietary fiber. The albedo + remains of flavedo reported a high content of TDF 75,97g/100g, the flavedo presented 58,23g/100g and the exhausted pulp results presented 66,95g/100g. All the fractions showed high IDF values between 50,82g/100g and 70,41g/100g. The IDF/SDF balance in the flavedo was 7.01 which was the best result compare to the exhausted pulp 23,79 and the albedo + remains of flavedo 12,69. The obtained results showed the good characteristics of the byproducts of orange as a source of total and insoluble dietary fiber